A decision support matrix in enhancing the quality of university’s remote learning: The Philippines settings during COVID-19 pandemic - Bucu, Gabriel C. (Animo Repository, 2022)
COVID-19 pandemic hampered the global economy and movement of people. Education, which is traditionally delivered in face-to-face settings, was severely affected. This dilemma led to the temporary closure of schools and universities worldwide. To ensure continuity of teaching delivery, academic institutions adopted complete online learning. The sudden adoption of remote learning gained additional feedback from various stakeholders. The Philippines, as a developing economy in Southeast Asia, had reached the mark in terms of the total no. of cumulative cases. Due to this prolonged mode, students shared increasing dissatisfaction towards remote learning. This research aims to understand the causal relationship of dissatisfaction factors, namely: 1) Academic Teaching, 2) Academic Support, 3) Accessibility, 4) Learner and 5) Community Social through Structural Equation Modelling (SEM) and 12 Engineering program outcomes designed by the Commission on Higher Education (CHED) in terms of knowledge, skills, and attitude. Results show that all dissatisfactions factors directly influence specific program outcomes. SO1, SO2, SO3, SO5, SO9, and SO11 were identified to be critical and need to be attended by HEIs. Then, through Focus Group Discussions, thematic analysis was conducted in determining the list of intervention strategies to address the critical outcomes. Specific strategies were streamlined through Analytical Hierarchy Process. This study generated decision support matrices per program outcomes infused with Service Recovery and Innovation principles.